Baseline concussion assessments can identify mental disorders: the SCAT-5 Symptom Evaluation compared to other screening tools in South African club rugby - Burger, James (Department of Psychiatry and Mental Health, 2023)
Mental disorders are common in athletes, but often go undiagnosed. Although mental health screenings are not routinely conducted in rugby, the Sport Concussion Assessment Tool – Fifth Edition (SCAT-5) is widely performed and measures affective, cognitive, sleep, and physical symptoms. This study investigated the psychometric properties of the SCAT-5 to explore its potential as a mental health screening tool. During preseason for the 2021 Western Province Super League A in South Africa, clinicians conducted mental health assessments of 71 adult male rugby union players. The SCAT-5 Symptom Evaluation, Baron Depression Screener for Athletes (BDSA), Athlete Psychological Strain Questionnaire (APSQ), Center for Epidemiologic Studies–Depression (CES-D), and Generalised Anxiety Disorder-7 (GAD-7) were compared to each other and to fully-structured diagnostic interviews by mental health professionals using the Mini International Neuropsychiatric Interview (MINI) 7.0.2. Lifetime MINI-defined mental disorders were common, being identified in 33.8% (95%CI 22.79 to 46.17%). Only 4.29% of these had a previous diagnosis. Exploratory Factor Analysis indicated a mental health construct of depression/anxiety being measured by the SCAT-5. The SCAT-5 had strong internal consistency ( = 0.94) and showed moderate convergent validity with the CES-D (r = 0.34; p = 0.008) and GAD-7 (r = 0.49; p < 0.0001). The area under the curve for identifying current disorders was 0.87 (p = 0.003). Since the SCAT-5 has the potential to identify depression and anxiety, it may allow mental health screening without the need for additional measures. Follow-up studies should further explore its discriminative ability in larger samples.